2019
DOI: 10.1037/aap0000159
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the silence: Perspectives on sexual violence among Indian American women.

Abstract: This study advances knowledge concerning 1.5-and second-generation Indian American women's perspectives and experiences of sexual violence. The findings underscore the complexity of sociocultural context and socialization and their impact on traumatic stress, coping, and help-seeking. They also help in guiding culturally informed interventions with 1.5and second-generation Indian American survivors of sexual violence. www.apa.org/pubs/journals/aap

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 39 publications
2
49
0
1
Order By: Relevance
“…When they raise children, these discourses and values are conveyed to their children (Adam & Schewe, 2007). There can be a lack of discussion about sex and sexual violence, while patriarchal norms are enforced (Tummala-Narra et al, 2019). These values are met with the messaging from western culture (Aumann & Titzmann, 2018).…”
Section: Discourses Of Sex and Sexual Violence In The Indian Diasporamentioning
confidence: 99%
See 3 more Smart Citations
“…When they raise children, these discourses and values are conveyed to their children (Adam & Schewe, 2007). There can be a lack of discussion about sex and sexual violence, while patriarchal norms are enforced (Tummala-Narra et al, 2019). These values are met with the messaging from western culture (Aumann & Titzmann, 2018).…”
Section: Discourses Of Sex and Sexual Violence In The Indian Diasporamentioning
confidence: 99%
“…Many Indian diaspora women face pressure from their families to refrain from dating because it tarnishes their and their family's reputations (Tummala-Narra et al, 2016;Wakil et al, 1981). One study by Tummala-Narra and colleagues (Tummala-Narra et al, 2019) found that survivors in the diaspora noted differences in defining sexual violence with the elders in their households. The survivors shared that they perceived more negative consequences for perpetrators of sexual violence in the US as compared to perpetrators in India (Tummala-Narra et al, 2019).…”
Section: Interaction With Western Culturementioning
confidence: 99%
See 2 more Smart Citations
“…In a qualitative study of nineteen 1.5-and second-generation Indian American women (Tummala-Narra et al, 2019), contextual factors such as socialization within family and ethnic and religious communities, and acculturative stress, influenced participants' perspectives and experiences of sexual violence, as well as their responses to violence. In particular, these women described the importance of adhering to family and community-based expectations regarding gender roles and sexual behavior, including the expectation that women should uphold family unity, even when victimized by sexual violence.…”
Section: Conceptualizations Of Interpersonal Violencementioning
confidence: 99%